Severe autoimmune hemolytic anemia in Covid-19 infection - Fehmi Hindilerden; Ipek Yonal-Hindilerden; Emre Akar; Zuhal Yesilbag; Kadriye Kart-Yasar (Mediterranean Journal of Hematology and Infectious Diseases)
xx